Computer modeling in the study of the effect of normalized quantities on the measurement accuracy of the quadratic transformation function - Shcherban’, Volodymyr; Korogod, Ganna; Kolysko, Oksana; Volivach, Antonina; Shcherban’, Yury; Shchutska, Ganna (Eastern-European Journal of Enterprise Technologies, 2022)
The research of the systems of equations of quantities describing, respectively, 5 and 6 measurement cycles revealed the peculiarities of redundancy formation. It is proved that the normalized temperature T1 has the greatest effect on the measurement result for both systems. In addition, it was found that in both systems, an increase in the reproduction accuracy of the normalized temperature T1 (with a constant reproduction error of T2) does not lead to a significant improvement in the results. Due to this, it can be argued on the use of non-precision normalized sources to reproduce the temperature T1. However, an order of magnitude increase in the reproduction accuracy of both normalized quantities T1 and T2 also increases the measurement accuracy by an order of magnitude. Computer modeling confirmed that for the redundant measurement equation (11) at the ratio Т1=Ті(0.0005•Ті+1) in the range (10÷200) °С, measurement with a relative error (0.01÷0.00003) % is provided. When applying the redundant measurement equation (13), the accuracy increases to 0.0059 % only at the end of the range. Based on the results obtained, it was found that the accuracy of redundant measurements is influenced by the type of equation itself, not their number. Processing of the results based on the redundant measurement equation, by the way, ensures the independence of the measurement result from the influence of absolute values of the transformation function parameters, as well as their deviations from nominal values under the influence of external destabilizing factors. Thus, there is reason to believe that it is possible to increase the accuracy of measurement in a wide range by observing the ratio between normalized and controlled quantities